Lessons from the failed constitutional referenda: The European Union needs to be politicized - Daniela Schwarzer (Stiftung Wissenschaft und Politik (SWP), 2005)
The rejection of the EU Constitution Treaty by the people of France and the Netherlands has thrown the European Union (EU) into a state of shock - now it is time to learn lessons from the referenda and the debates conducted in the lead-up. France in particular went through a passionate debate about the future of the EU which raised a number of major issues. It was not fundamental anti-EU sentiment that led to rejection of the Treaty but dissatisfaction with the French government's domestic policies, coupled with divergent ideas about the future shape of the EU. The results in France and the Netherlands revealed an alienation between the population and the EU which has been perceptible for several years, for example in European parliamentary elections. If the EU is to regain legitimacy in the eyes of the population, it must be politicized and entrenched as a democratic project. (SWP-Comments / SWP)
Keywords: 320